The Prevalence and Psychosocial Factors of Problematic Smartphone Use Among Chinese College Students: A Three-Wave Longitudinal Study - Wang, Anqi; Wang, Zhen; Zhu, Ya; Shi, Xuliang (Frontiers in Psychology, 2022)
Problematic smartphone use (PSU) in college students has been a major public health concern in modern society, which may also lead to adverse health outcomes. Using a three-wave longitudinal study design, the current study aimed to examine the prevalence and psychosocial factors of PSU in a large sample of Chinese college students. The data used in this study was obtained from an ongoing longitudinal study in Guangdong, China. In the current study, a total of 7,434 freshmen and sophomores who completed the first three surveys were included. Self-administered questionnaires were used to assess PSU, possible social anxiety disorders, depressive symptoms, loneliness, family conflicts, academic stress and some demographic characteristics. Generalized estimating equation (GEE) models were performed to determine the risk factors associated with PSU. The results showed that 65.8%, 58.1% and 52.8% of college students reported PSU at three waves, with an apparent downward trend. Female students reported higher prevalence rates of PSU than males. Depressive symptoms, possible social anxiety disorders, loneliness, family conflicts and high academic pressure were important risk factors for PSU. Early intervention and identification of those who show signs of PSU may prevent the development of maladaptive coping responses and addictive behaviors, so as to prevent future negative psychosocial consequences.